FRAUD PENTAGON ANALYSIS ON DETERMINAND FRAUD FINANCIAL STATEMENT - Shlof, Mohamed A. (Jurnal Kewirausahaan dan Inovasi, 2023)
The purpose of this study was to determine the effect of Pressure on Fraudulent Financial Statements, Opportunity on Fraudulent Financial Statements, Rationalization on Fraudulent Financial Statements, Competence on Fraudulent Financial Statements, and Arrogance on Fraudulent Financial Statements. The population in this study were employees of Ahlia Cement Company. Structural Equation Modeling (SEM) which is run through the Partial Least Squares Structural Equation Modeling (PLS-SEM) program is an analytical technique used to examine the data in this study. The results showed that Pressure affects Fraudulent Financial Statements, Opportunity influences Fraudulent Financial Statements, Rationalization influences Fraudulent Financial Statements, Competence influences Fraudulent Financial Statements, Arrogance influences Fraudulent Financial Statements. For future research, it is hoped that it will enrich other independent variables which are expected to influence fraudulent financial statements, for example changes in total assets, company debt, changes in accounts receivable, and others. The next research is expected to multiply and expand the sample in the study, for example using all manufacturing companies, so that the sample obtained is wider and can describe the actual conditions.